Pediatric burns in Israeli natives versus asylum seekers living in Israel: Lessons learned. Issue 5 (August 2018) - Zissman, Sivan; Orgil, Matan; Ben-Amotz, Oded; Gur, Eyal; Arad, Ehud; Leshem, David
Highlights: Although the asylum seekers represent 6% of the Tel Aviv area population they make up 10% of its burns cases. There was no significant different regarding: young age; male–female ratio; scald type's burns; limb involvement. Hospitality rate and duration was significant higher among asylum seekers as well as family burden. Emphasizes the need for prevention, education, and accessible and affordable treatment in risk group populations. Abstract: Background: Burn injuries are one of the leading causes of morbidity and mortality in the pediatric population. In early childhood, burns have a wide range of adverse long-term consequences ranging from functional impairment to psychological implications. Children from low-income and middle-income countries are at a higher risk of suffering from burn injuries. In the last 10 years the population of asylum seekers from low-income countries in Israel has increased dramatically. About 25, 000 or 60% of asylum seekers are living in the Tel Aviv area, making up roughly 6% of the city's total population (about 405, 000). Aim: A retrospective study aimed to profile the pediatric burn injuries treated at the Tel Aviv Sourasky Medical Center over the last 9 years in an effort to examine the distinct characteristics of African asylum seekers who suffer burn injuries in comparison with Israeli nationals. Patients & Methods: Medical records of 876 patients under the age of 18 years presenting between 2007–2015 were retrospectively reviewed. The parameters collected included gender, causality, total body surface area (TBSA), burn depth and patient outcome. Conclusions: There was no significant difference regarding: age; male-female ratio; scald-types burns; limb involvement. However, hospitalization and length of hospital stay were significantly higher among asylum seekers, as was family burden. Questions may be raised regarding prevention, education & social support. Our research provides a small glimpse into the world of asylum seekers in Israel. We hope it will serve as a window into the much grander problems that this population faces on a daily basis.